Meningkatkan Layanan Intervensi Anak Berkebutuhan Khusus Di Sekolah Dasar Negeri 31/II SKB - firman, endri; Jati, Imam Ikhsanul; Andriani, Opi; Prahagia, Yelvia (Jurnal Pendidikan Vokasi dan Seni, 2023)
The aim of this research is to describe ways to improve intervention services for children with special needs at SKB 31/II State Elementary School. This study uses a qualitative method. Data collection techniques include: observation and interviews. The subject of this research is a special supervising teacher for ABK. The research results show that in developing intervention services there are several things that need to be considered and considered, namely population, area, continuous services, and theoretical basis. By developing this program, the quality of intervention services for children with special needs in elementary schools can be improved.